Ethyl Acetate Fraction of Bixa orellana and Its Component Ellagic Acid Exert Antibacterial and Anti-Inflammatory Properties against Mycobacterium abscessus subsp. massiliense - Roberval Nascimento Moraes-Neto; Gabrielle Guedes Coutinho; Ana Caroline Santos Ataíde; Aline de Oliveira Rezende; Camila Evangelista Carnib Nascimento; Rafaela Pontes de Albuquerque; Cláudia Quintino da Rocha; Adriana Sousa Rêgo; Maria do Socorro de Sousa Cartágenes; Ana Lúcia Abreu-Silva; Igor Victor Ferreira dos Santos; Cleydson Breno Rodrigues dos Santos; et al. (MDPI AG, 2022)
Mycobacterium abscessus subsp. massiliense (Mabs) causes chronic infections, which has led to the need for new antimycobacterial agents. In this study, we investigated the antimycobacterial and anti-inflammatory activities of the ethyl acetate fraction of Bixa orellana leaves (BoEA) and ellagic acid (ElAc). In silico analysis predicted that ElAc had low toxicity, was not mutagenic or carcinogenic, and had antimicrobial and anti-inflammatory activities. Apparently, ElAc can interact with COX2 and Dihydrofolate reductase (DHFR) enzymes, which could explain both activities. In vitro analysis showed that BoEA and ElAc exerted antimicrobial activity against Mabs (minimum inhibitory concentration of 1.56, 1.56 mg/mL and bactericidal concentration of 6.25, 3.12 mg/mL, respectively. Clarithromycin showed MIC and MBC of 1 and 6 µg/mL). Treatment with BoEA or ElAc increased survival of Tenebrio molitor larvae after lethal infection with Mabs and reduced carrageenan-induced paw edema in mice, around 40% of edema volume after the fourth hour, similarly to diclofenac. In conclusion, BoEA and ElAc exert antimicrobial effects against Mabs and have anti-inflammatory effects, making them potential sources of antimycobacterial drugs. The biological activities of ElAc may be due to its high binding affinities predicted for COX2 and DHFR enzymes.